An Example of Pragmatic Analysis in Natural Language Processing: Sentimental Analysis of Movie Reviews - SÜTCÜ, CEM SEFA; AYTEKİN, ÇİĞDEM (EDITOGRAFICA S R L, 2019)
Natural Language Processing (NLP) studies are one of the most exciting applications of artificial intelligence and it is foreseen that NLP will cause new and revolutionist changes in humancomputer interaction. In this aspect, NLP is analyzed in five different segments: Phonology, Morphology, Syntax, Semantics, Pragmatics Analysis. In this paper, a sentimental analysis will be conducted using movie reviews left by users on beyazperde.com. The sentimental analysis allows to automatically draw conclusions about the mood from text data. Thus, numerous reviews left on a movie can be sorted as a positive or negative mood without the need of reading all of them one by one. The ability to sort the reviews automatically according to their mood is invaluable to those who are considering watching the said movie, actors\actresses, producers and advertisers. Such application arms media companies with new and improvable opportunities to create effective strategies. In this aspect, viewer expectations can be analyzed, and this information can be utilized for the upcoming program projects. Importance of communications and information technologies is undeniable. It is foreseen that this paper will aid the production of information processing in Turkish.
Keywords: Natural Language Processing; Artificial Intelligence; Sentimental Analysis; Movie Reviews